Thrombus aspiration in patients with ST-segment elevation myocardial infarction: a literature review - V. V. Ryabov; Yu. O. Samoilova; A. E. Gombozhapova; M. A. Sirotina; L. N. Maslov (Кардиоваскулярная терапия и профилактика, 2023)
Thrombus aspiration has not shown significant advantages over routine percutaneous coronary intervention in reducing the incidence of major adverse cardiovascular events (MACEs) in the general heterogeneous population of patients with ST-segment elevation myocardial infarction (STEMI). However, it is still practically used in cases of massive coronary artery thrombosis. This review presents the results of studies on thrombus aspiration in patients with STEMI with a focus on favorable outcomes. According to the literature data, thrombus aspiration proved to be effective in following groups of STEMI patients: 1) patients with hyperglycemia; 2) patients with high D-dimer levels; 3) elderly and frail patients. In order to assess the effectiveness of reperfusion, only angiographic characteristics are still used in routine practice, while multimodal imaging methods have not yet become widespread. Moreover, optimal and unified thrombus aspiration protocols have not yet been developed.